Assessment of the Availability and Accuracy of Dosing Devices Packaged with Oral Liquid Medications in the Ho Municipality of Ghana. (20th October 2022) - Saaka, Yussif; Nyamadi, David M.; Amekyeh, Hilda; Mensah, Adelaide
Abstract : Introduction . Administering the right dose of medications is essential in avoiding potentially life-threatening adverse drug reactions. Industry guidelines for manufacturers of oral, over-the-counter, and liquid medications recommend including dose-delivery devices with packaging to limit dosing inaccuracy. This study describes the prevalence and accuracy of dosing devices packaged with oral liquid medications in the Ho municipality of Ghana. Methods . Dosing device accuracy was determined after deviation of the measured volume from the expected volume was evaluated using the United States Pharmacopoeia criteria. Results . A total of 78.6% of the oral liquid medications were packaged with a dosing device. The most common dosing devices were cups (83.6%), followed by spoons (14.3%), droppers (1.4%), and syringes (0.7%). The volumes measured with cups (5.14 ± 0.52 mL, p = 0.006 ) and spoons (5.3 ± 0.67 mL, p < 0.001 ) were significantly different from the desired 5 mL volume; this was dissimilar to the volume measured using syringes (5.01 ± 0.02 mL, p > 0.999 ). Further, the measured volumes for 38.6% and 72.2% of the cups and spoons, respectively, deviated by more than 15% of 5 mL. Conclusion . Dosing cups and spoons are associated with significant inaccuracy. Yet, manufacturers continually favour them over syringes in packaging for oral liquid medications. This is unacceptable and of considerable concern due to the risk of variations in therapeutic outcomes. Therefore, strict regulatory directives on the inclusion of accurate dosing devices in the packaging of oral liquid medicines are needed to reduce the possibility of medication errors.